Public debt-investment nexus: The significance of investment-generation policy in West Africa - Fisayo Fagbemi; Opeoluwa A. Adeosun (African Governance and Development Institute (AGDI), 2020)
The study examines the long run relationship and interconnections between public debt and domestic investment in 13 West African countries from 1986-2018. Using panel Panel Dynamic Least Squares (DOLS) and Panel Fully Modified Least Squares (FMOLS), debt (% of GDP) and external debt have an insignificant effect on investment in the long run, suggesting the negligible effect of public debt on the level of investments. But domestic investment Granger causes public debt indicators, implying that there is unidirectional causality. This suggests that any investmentgeneration policy could engender a rise in public borrowing, although such public loans might not be effective when there is pervasive mismanagement of public funds, as public debts need to be well managed for ensuring improved investment. Thus, the study suggests that maintaining a strong and effective debt-investment nexus requires fiscal consolidation efforts across countries, as such could lead to enhanced institutional capacity and sustainable investment-generation policy.
Keywords: H63; E22; H30; 330; Public debt; investment; fiscal policy; cointegration analysis; West Africa